The characteristic and prognostic role of blood inflammatory markers in patients with Huntington’s disease from China - Xia, Jie-Qiang; Cheng, Yang-Fan; Zhang, Si-Rui; Ma, Yuan-Zheng; Fu, Jia-Jia; Yang, Tian-Mi; Zhang, Ling-Yu; Burgunder, Jean-Marc; Shang, Hui-Fang (Frontiers in Neurology, 2024)
Objectives This study aims to elucidate the role of peripheral inflammation in Huntington’s disease (HD) by examining the correlation of peripheral inflammatory markers with clinical manifestations and disease prognosis. Methods This investigation involved 92 HD patients and 92 matched healthy controls (HCs). We quantified various peripheral inflammatory markers and calculated their derived metrics including neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), and systemic immune-inflammation index (SII). Clinical assessments spanning cognitive, motor, and disease severity were administered. Comparative analysis of inflammatory markers and clinical correlations between HD and controls was performed. Kaplan–Meier survival analysis and Cox regression model were used to assess the effect of inflammatory markers on survival. Results The study revealed that HD patients had significantly reduced lymphocyte counts, and LMR. Conversely, NLR, PLR, and SII were elevated compared to HCs. Lymphocyte levels inversely correlated with the age of onset and monocyte levels inversely correlated with the UHDRS-total functional capacity (TFC) scores. After adjusting for age, sex, and CAG repeat length, lymphocyte count, NLR, PLR, and SII were significantly correlated with the progression rate of TFC scores. Elevated levels of white blood cells and monocytes were associated with an increased risk of disability and mortality in the HD cohort. Conclusion Our findings indicate that HD patients display a distinct peripheral inflammatory profile with increased NLR, PLR, and SII levels compared to HCs. The peripheral inflammation appears to be linked with accelerated disease progression and decreased survival in HD.